Simulation study of a low-cost Slide-Through PET scanner based on narrow flat panels with monolithic detectors - Dhaenens, Elke; Vervenne, Boris; Abi Akl, Maya; Maebe, Jens; Vanhove, Christian; Vandenberghe, Stefaan (Frontiers in Physics, 2026)
BackgroundPatient throughput in conventional PET systems is constrained by limited system sensitivity and the need for bed positioning. This study proposes a cost-effective Slide-Through PET (ST-PET) design based on two narrow monolithic LYSO detector panels with depth-of-interaction (DOI) readout. Each vertical panel has a length of 190.5 cm and consist of a 20.9-cm-wide top part for scanning the torso, and a 10.3-cm-wide bottom part to image the legs. The panels translate laterally relative to a standing patient to cover a 73.9 cm-wide field of view.MethodsThe ST-PET system was simulated in GATE and compared with two reference designs: a cylindrical PET system, and a wide static flat-panel PET. All systems used identical high-resolution monolithic LYSO detectors (300 ps time-of-flight, 2.67 mm DOI). Different panel motion strategies were explored for the ST-PET, and system performance was assessed in terms of sensitivity, spatial resolution, and image quality using NEMA image quality and anthropomorphic XCAT phantoms.ResultsParallel motion of the panels ensured complete anatomical coverage, whereas other motion strategies provided focused but incomplete sampling. Sensitivity for a whole-body water phantom was 1.66 cps/kBq in the upper region and 0.52 cps/kBq in the lower region, whereas the cylindrical reference system provided 1.05 cps/kBq in both regions. The ST-PET system achieved sub-3 mm spatial resolution in the center of the field of view. Image quality varied between the upper and lower ST-PET sections, with superior contrast recovery and noise characteristics in the torso region. Shorter scan times suffice using the ST-PET to obtain similar noise characteristics in the lung and liver than with the cylindrical reference. Mild elongation artifacts are observed in the IQ and XCAT images for both flat-panel systems.ConclusionST-PET demonstrates the feasibility of a compact sliding-panel geometry that delivers high spatial resolution and competitive sensitivity while enabling workflow efficiencies that could enhance throughput in clinical PET. Additional improvements in TOF resolution are needed to mitigate limited angle artifacts, which would further enhance the relevance of such a narrow-panel geometry.